(untitled) - Kee, Joyce LeFever (St. Louis, 2004)
This book provides comprehensive coverage of dosage calculations used in nursing practice, including applications not only for the general patient care areas, but also for specialty units such as pediatrics, critical care, labor and delivery, and the community. In addition, it is the only text on the market that presents all four major dosage calculation methods (ratio/proportion, formula, fractional equation, and dimensional analysis).
Keywords: Pharmaceutical arithmetic,Nursing,Pharmaceutical Preparations--administration & dosage,Mathematics; Mathematics,Nurses’ Instruction,Nurses’ Instruction